Jorid Linvik's big book of knits for kids : over 45 distinctive Scandinavian patterns - Linvik, Jorid (Trafalgar Square Books, 2020)
Delightful, personalizable handknit children's accessories from Jorid Linvik. Indulge the kids in your life with their favorite things. Bestselling knit designer Jorid Linvik (author of knitting's popular "Big Book" series) makes it easy with handknit patterns for hats, mittens, gloves, and socks that will fit little heads, hands, and feet just right. With over 40 delightful projects, overflowing with Jorid's undeniable talent for designs bursting with warmth, charm, and color, it's never been easier to keep kids from newborn to eight years old comfy and cozy, with winter accessories they'll want to put on!